Проблемы формирования орфоэпической компетенции курсантов при обучении русскому языку в рамках совершенствования уровня культуры речи - Саримсакова, Н.К (SCIENCE and SOCIETY, 2021)
The article actualizes the problems of the formation of orthoepic competence of cadets within the framework of improving the level of speech culture. The author considers this problem in the framework of the formation of the orthoepic competence of future military personnel. The article substantiates the growing importance of the formation of orthoepic competence, lists the main reasons indicating the need to improve professionally oriented oral speech. The article also presents the methodological means of forming the orthoepic competence of cadets, provides examples of their use. The author substantiates that the formation of the orthoepic competence of cadets at the stage of initial professional self-realization is an important and constant task, since the formation of stable pronunciation standards and the proper level of development of speech culture will ensure the normal functioning of monologic and dialogical oral speech activi- ty in the future.
Keywords: Russian language; speech culture; orthoepic competence; cadets; professional-contextual speech activity Методологическая основа успешного овладения ор- стоянием русского языка; общими тенденциями языко- фоэпической компетенцией на этапе профессио- вого развития общества; а также снижением уровня нального образования заключена в одном из признан- культуры речи и общения в военной среде. Это обу-